The Covenant of Moakhat (Brotherhood - Roohollah Bahrami (تاریخ اسلام, 2001)
The present paper, which is an introduction on the formation of the Covenant of Brotherhood in Medina, examines and comments upon the fraternal viewpoint and the rite of brotherhood in early Islam. While dealing with the intellectual and philosophical principles of the concept of religious brotherhood, the paper tries to shed light on the role of this concept and phenomenon in creating unity in the early Muslim community. For this purpose, the Qura'n's call to religious brotherhood, the Prophet's Sirah and practice in elevating the racist Arab bias of blood brotherhood to the level of religious brotherhood, and this initiative of the establishment of the covenant of Brotherhood between Muslims are studied and reviewed.